Relationship between raised BMI and sugar sweetened beverage and high fat food consumption among children. - Millar, L; Rowland, B; Nichols, M; Swinburn, B; Bennett, C; Skouteris, H; Allender, S (2014)
OBJECTIVE: Longitudinal evidence of relationships between unhealthy diets and BMI in children is crucial for appropriately targeting obesity prevention activities. The objective was to determine the relationship between frequency of consumption of sugar sweetened beverages (SSBs) and high fat foods (HFFs) and body weight in Australian children aged from 4 to 10 years. METHODS: Data from 4,164 children participating in four waves (wave 1, 2004; wave 2, 2006; wave 3, 2008; and wave 4, 2010) of the Longitudinal Study of Australian Children were analyzed. A multi-level growth model tested relationships between consumption of SSB and HFF and BMI z-scores. RESULTS: BMI z-scores were associated with daily consumption of HFF, SSB and maternal BMI independent of BMI z-scores at wave 1 (baseline); with each additional occurrence of SSB and HFF consumption intake per day, BMI z-score increased by 0.015 U (P < 0.01) and 0.014 U (P < 0.001), respectively. With each additional maternal BMI unit, BMI z-score increased by 0.032 (P < 0.001). CONCLUSIONS: Higher BMI z-scores were strongly associated with the consumption of SSBs and HFFs. Future efforts to prevent obesity should consider urgent action to address the impact of the consumption of SSBs and HFFs in childhood.